Universal Tendencies of European Integration: Culture Analysis - B. Kabylinskiy (Евразийская интеграция: экономика, право, политика, 2019)
Article is devoted to analysis of such Eurasian integration aspect as universal tendencies of social, economic and politic evolution from culturological research view. Author concentrates on changes in ways of translating information, subjects of integration, transit condition of modernizing national and state idea. In the conclusion author offers possibility to create new methodology of analyzing European integration.